2022
DOI: 10.3390/insects13030241
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptome Investigation of Nosema ceranae Infecting Eastern Honey Bee Workers

Abstract: Apis cerana is the original host for Nosema ceranae, a widespread fungal parasite resulting in honey bee nosemosis, which leads to severe losses to the apiculture industry throughout the world. However, knowledge of N. ceranae infecting eastern honey bees is extremely limited. Currently, the mechanism underlying N. ceranae infection is still largely unknown. Based on our previously gained high-quality transcriptome datasets derived from N. ceranae spores (NcCK group), N. ceranae infecting Apis cerana cerana wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 44 publications
2
0
0
Order By: Relevance
“…Therefore, the upregulation of AAJ76_1600052943 and AAJ76_2000141845 might also play roles similar to those mentioned above to facilitate spore germination and mature spore development. The highly expressed SPW was consistent with our previous study on N. ceranae gene expression in A. mellifera [ 33 ] and the research on the N. ceranae gene expression in A. cerana, suggesting a significant role for SPW during N. ceranae infection [ 53 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Therefore, the upregulation of AAJ76_1600052943 and AAJ76_2000141845 might also play roles similar to those mentioned above to facilitate spore germination and mature spore development. The highly expressed SPW was consistent with our previous study on N. ceranae gene expression in A. mellifera [ 33 ] and the research on the N. ceranae gene expression in A. cerana, suggesting a significant role for SPW during N. ceranae infection [ 53 ].…”
Section: Discussionsupporting
confidence: 90%
“…The results indicated that a greater upregulation of N. ceranae’s common and stage-specific genes was found in the initial infectious stage, whereas more genes of N. ceranae were suppressed in the late stage of infection. This tendency was similar to the study of N. ceranae gene expression in Apis cerana, suggesting that the N. ceranae genes were expressed at an early infection stage, followed by the gene expression profile of N. ceranae switching from the merogony to sporogony stages [ 53 ]. Microsporidia lack mitochondria, and the loss of most metabolic pathways might involve an alteration of gene expression during the course of infection; therefore, host-generated ATP would be imported to support their metabolism [ 54 , 55 ].…”
Section: Discussionsupporting
confidence: 83%